find out the sum and the multiplication of the root of the polynomial:
![a( {x }^{2} + 1) - x( {a}^{2} + 1) a( {x }^{2} + 1) - x( {a}^{2} + 1)](https://tex.z-dn.net/?f=a%28+%7Bx+%7D%5E%7B2%7D++%2B+1%29+-+x%28+%7Ba%7D%5E%7B2%7D++%2B+1%29)
Answers
✰ p(x) =
✰we need to find the relationship between the zeroes and coefficients.
a(x² + 1) - x(a² + 1)
ax² - xa² + a - x
xa (x - a) -1(x - a)
(xa - 1)(x - a)
So,
The zeroes of the given polynomial:-
xa - 1 = 0
xa = 1
x = 1/a
Or
x - a = 0
x = a
Now,
Let α and β are the zeroes of the given polynomial.
Let α = 1/a
and β = a
Sum of zeroes = α + β
1/a + a
Product of zeroes:- αβ
1/a × a
1
Now,
Verification:-
p(x) = ax² -(a² + 1)x + a
sum of zeroes:-
α + β = - b/a
Product of zeroes:-
αβ = c/a
1/a × a = a/a
1 = 1
LHS = RHS
hence , relationship is verified.
━━━━━━━━━━━━━━━━━━━━━━━━━
Step-by-step explanation:
Given -
- p(x) = a(x² + 1) - x(a² + 1)
To Find -
- Sum and multiplication of the root of the polynomial.
Now,
→ a(x² + 1) - x(a² + 1) = 0
→ ax² + a - xa² - x = 0
→ ax² - xa² - x + a = 0
→ ax(x - a) - 1(x - a)
→ (ax - 1)(x - a)
Zeroes are :-
→ ax - 1 = 0 and x - a = 0
→ x = 1/a and x = a
Then,
The sum of the root of the polynomial is
→ 1/a + a
→ a² + 1/a
And
The product of the root of the polynomial is
→ 1/a × a
→ 1
Hence,
The sum of the root of the polynomial is 1 + a²/a
And
The product of the root of the polynomial is 1